CVLA STUDY: CAPILLARY AND VENOUS LACTATE AGREEMENT—A PILOT OBSERVATIONAL STUDY. Issue 12 (23rd November 2015) - Datta, D; Grahamslaw, J; Gray, AJ; Graham, C
Abstract : Objectives & Background: Blood lactate measurement is used as a marker of the severity of illness in patients presenting to the Emergency Department (ED): higher lactate levels are associated with increased mortality. Arterial lactate is the gold standard of measurement, however is increasingly being substituted by peripheral venous lactate (PV-LACT) measurement. Capillary lactate (CAP-LACT) measurement has been used in the paediatric ED and in sports science; however it has not been thoroughly tested in the adult ED. Until recently there has not been a medically certified point-of-care meter to use in clinical settings. The Nova Biomedical StatStrip Lactate meter can measure CAP-LACT with a disposable strip system similar to the routine measurement of capillary glucose in the ED. CAP-LACT has the potential to allow quick lactate recording by all triage staff with minimal equipment, whilst being more acceptable to the patient as an investigation. We aim to collect pilot data investigating the agreement between CAP-LACT and PV-LACT in the ED. This will allow us to determine feasibility and statistical power for the design of a definitive study. Methods: We performed a prospective observational cohort study of 99 consented patients between October and December 2014 requiring PV-LACT measurement as part of their routine clinical care to a single UK NHS ED (110, 000 adult attendances annually). Paired CAP-LACT and PV-LACT (in mmol/L) was recorded, and level of agreement determined by Bland-Altman analysis. Results: The median lactate measurements were 1.3 for PV-LACT and 1.6 for CAP-LACT (table 1 ). Bland-Altman analysis noted a mean difference (CAP-LACT-PV-LACT) of 0.23 mmol/L, with 95% limits of agreement from −1.86 to 2.33 (figure 1). Median PV-LACT tourniquet time was 1 minute, with median time between samples being 4 minutes (interquartile range 2–4 minutes) (table 2 ). Only 4 samples had a lactate greater than 4 mmol/L. Conclusion: The results show that there is potential for CAP-LACT to replace other methods of lactate measurement. However the wide 95% limits of agreement and lack of high lactate values means further definitive studies need to be conducted before we can use CAP-LACT in routine practice. The pilot data will allow the design of this definitive study. Capillary lactate could potentially revolutionise triage by allowing wider minimally invasive screening of patients presenting to the EDTable 1 Table 2 Figure 1 .